2007
DOI: 10.1152/ajpheart.01378.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitochondrial permeability transition improves functional recovery and reduces mortality following acute myocardial infarction in mice

Abstract: Inhibition of mitochondrial permeability transition pore (mPTP) opening by cyclosporin A or ischemic postconditioning attenuates lethal reperfusion injury. Its impact on major post-myocardial infarction events, including worsening of left ventricular (LV) function and death, remains unknown. We sought to determine whether pharmacological or postconditioning-induced inhibition of mPTP opening might improve functional recovery and survival following myocardial infarction in mice. Anesthetized mice underwent 25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(112 citation statements)
references
References 53 publications
(64 reference statements)
4
105
2
1
Order By: Relevance
“…C57BL/6 J (male, 8-10 weeks old) were anesthetized by intraperitoneal mixture of 70 mg/kg pentobarbital sodium and 0.1 mg/kg buprenorphine as described previously. 7,[38][39][40] The animals were orally intubated, ventilated and body temperature was maintained at 37°C. A left thoracotomy was performed in the fourth intercostal space.…”
Section: Gsk3β Regulates Ca 2+ Transfer At Mams L Gomez Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…C57BL/6 J (male, 8-10 weeks old) were anesthetized by intraperitoneal mixture of 70 mg/kg pentobarbital sodium and 0.1 mg/kg buprenorphine as described previously. 7,[38][39][40] The animals were orally intubated, ventilated and body temperature was maintained at 37°C. A left thoracotomy was performed in the fourth intercostal space.…”
Section: Gsk3β Regulates Ca 2+ Transfer At Mams L Gomez Et Almentioning
confidence: 99%
“…Myocardial infarct size was then determined by triphenyltetrazolium staining as described previously. 7,[38][39][40] Statistical analysis. Data are presented as mean ± S.E.M., unless otherwise specified.…”
Section: Gsk3β Regulates Ca 2+ Transfer At Mams L Gomez Et Almentioning
confidence: 99%
“…Interestingly, in this same study, delaying NIM811 administration by 12 h following injury was effective in preventing cytoskeletal degradation. Finally, NIM811 significantly reduced reperfusion injury following experimental acute myocardial infarction [94,96,99]. Collectively, the findings of these studies suggest that an approach that targets the mPTP can be generalized to several models of cell death.…”
Section: Targeting the Mptp In Acute Scimentioning
confidence: 75%
“…Numerous experimental studies and clinical observations have demonstrated that the immunosuppressant cyclosporin A (CsA), which inhibits mPT and promotes mitochondrial function, may be of therapeutic benefit in the treatment of acute traumatic brain injury (TBI), SCI, cerebral ischemia, and reperfusion injury following acute myocardial infarction [94][95][96][97][98][99][100][101][102][103]. Phase I clinical trials for the acute treatment of severe TBI have been performed, and follow-up trials have been proposed [104].…”
Section: Targeting the Mptp In Acute Scimentioning
confidence: 99%
“…68 involved in the acute loss of neurons and cardiomyocytes induced by ischemia/re-oxygenation and excitotoxicity. 23,[58][59][60] The molecular mechanisms that trigger the opening of the PTPC in these settings share a prominent oxidative component and the cytosolic accumulation of Ca 2+ ions, which de facto are tightly linked to each other. 61 During the last decades, several proteins have been suggested to constitute core components of the PTPC, including various isoforms of VDAC and ANT as well as CYPD, yet only the latter appears to be truly required for MPT in vivo.…”
Section: Methodsmentioning
confidence: 99%